Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18410/jebmh/2017/803
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Menstrual Problems and Menstrual Hygiene Practices Among College Going Unmarried Girls in Chandigarh, India

Abstract: BACKGROUND Menstruation is a vital part of the reproductive health of a woman. There is evident neglect of problems related to menstruation especially in young girls and they are lacking scientific knowledge regarding menstruation. The study was undertaken with the objective to assess the prevalence & patterns of menstrual problems, knowledge, belief, restrictions, menstrual hygiene and treatment seeking practice among college going unmarried girls of Chandigarh. MATERIALS AND METHODS A stratified multistage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly, nine out of ten participants in a study conducted in Northeast Ethiopia had prior information, and the majority of them cited their sisters as the source of information 26. A previous report based in Chandigarh, India also reported a very high knowledge prevalence, and more than half of the participants cited mothers and sisters as the source of menstrual knowledge 27 . Higher knowledge status in a family coupled with lower levels of apprehension while discussing menstruation with their daughters could be associated with greater literacy levels of the mothers and the presence of sister(s).…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, nine out of ten participants in a study conducted in Northeast Ethiopia had prior information, and the majority of them cited their sisters as the source of information 26. A previous report based in Chandigarh, India also reported a very high knowledge prevalence, and more than half of the participants cited mothers and sisters as the source of menstrual knowledge 27 . Higher knowledge status in a family coupled with lower levels of apprehension while discussing menstruation with their daughters could be associated with greater literacy levels of the mothers and the presence of sister(s).…”
Section: Discussionmentioning
confidence: 77%
“…Other studies reported similar results. 16,[24][25][26][27] But in other similar studies conducted in Rajasthan, only 25% and 28% reported the use of readymade sanitary pads respectively. 3,28 Only 13% reported using cloth in the study while other studies found that cloth was used as the major absorbent.…”
Section: Resultsmentioning
confidence: 99%
“…In social context people avoid talking about menstruation due to stigma or taboo, girls might not fully understand what's happening to their bodies. Parents' reluctance to openly discuss these topics prevents adolescent girls from getting the information they need (Sachdeva et al, 2017). Thérèse and Maria (2010) explores that women and girls disproportionately shoulder the burden of poor health, spend considerable time fetching water, and lack privacy for defecation and personal hygiene.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Access to clean absorbents, together with facilities for replacing, washing, or discarding them as needed, and soap and water for cleansing the body and absorbents are essential components of effective menstrual hygiene management (MHM). Sachdeva et al (2017) claims that menstruation, a natural physiological occurrence exclusive to females, commences during adolescence. Similarly, Santina et al (2013) argue that the menstrual cycle is a regular, natural physiological occurrence.…”
Section: Introductionmentioning
confidence: 99%